2007
DOI: 10.1016/j.molcel.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Elongation by RNA Polymerase I Is Linked to Efficient rRNA Processing and Ribosome Assembly

Abstract: The synthesis of ribosomes in eukaryotic cells is a complex process involving many nonribosomal protein factors and snoRNAs. In general, the processes of rRNA transcription and ribosome assembly are treated as temporally or spatially distinct. Here, we describe the identification of a point mutation in the second largest subunit of RNA polymerase I near the active center of the enzyme that results in an elongation-defective enzyme in the yeast Saccharomyces cerevisiae. In vivo, this mutant shows significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
124
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 56 publications
13
124
0
Order By: Relevance
“…By using qChIP analysis to evaluate Pol I loading onto the rDNA in combination with pulse metabolic labelling to measure newly synthesized 47S pre-rRNA, we demonstrated that acute serum withdrawal from exponentially growing cells inhibited 47S prerRNA synthesis without changing Pol I loading onto the rDNA. This suggests that growth factor signalling is required for transcription elongation and possibly cotranscriptional processing of rRNA, which is known to be coupled to elongation in yeast [36,50]. Consistent with this finding, enhanced transcription initiation mediated by Rrn3 overexpression was not sufficient to promote full length 47S pre-rRNA synthesis under serum starvation conditions, despite elevated Pol I loading at the rDNA.…”
Section: Accepted Manuscript 18mentioning
confidence: 65%
See 2 more Smart Citations
“…By using qChIP analysis to evaluate Pol I loading onto the rDNA in combination with pulse metabolic labelling to measure newly synthesized 47S pre-rRNA, we demonstrated that acute serum withdrawal from exponentially growing cells inhibited 47S prerRNA synthesis without changing Pol I loading onto the rDNA. This suggests that growth factor signalling is required for transcription elongation and possibly cotranscriptional processing of rRNA, which is known to be coupled to elongation in yeast [36,50]. Consistent with this finding, enhanced transcription initiation mediated by Rrn3 overexpression was not sufficient to promote full length 47S pre-rRNA synthesis under serum starvation conditions, despite elevated Pol I loading at the rDNA.…”
Section: Accepted Manuscript 18mentioning
confidence: 65%
“…Emerging evidence however, suggests that the elongation step in Pol I transcription is important for the overall control of rRNA synthesis rate as well as ensuring efficient rRNA processing [33][34][35][36][37]. In contrast to the model of initiation regulation,…”
Section: Accepted Manuscriptmentioning
confidence: 95%
See 1 more Smart Citation
“…MTERF3 and mtRNA polymerase were both identified as interacting with RNMTL1, possibly mediated by RNA structures (Table 1). Elegant experiments have shown that the rate of transcription by nuclear RNA polymerase I is coupled to events in rRNA modification and ribosome assembly (56). MTERF3 and the complex of MTERF4-NSUN4 may operate in a similar manner in mitochondria (19).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that the production of ribosomes depends on a kinetic balance between the rate of rRNA synthesis and the rates of rRNA folding and maturation. 44 DFC is generated by elongation of rDNA transcription and the first cleavage-modification steps of pre-rRNAs. Late cleavage-processing steps and assembly of the large ribosome subunits generate the GC.…”
Section: Discussionmentioning
confidence: 99%